Decreased mitochondrial activity in the demyelinating cerebellum of progressive multiple sclerosis and chronic EAE contributes to Purkinje cell loss - Kelley C. Atkinson; Shane Desfor; Micah Feri; Maria T. Sekyi; Marvellous Osunde; Sandhya Sriram; Saima Noori; Wendy Rincón; Britany Bello; Seema K. Tiwari-Woodruff (Proceedings of the National Academy of Sciences, 2025)
In multiple sclerosis (MS), cerebellar gray matter atrophy, white matter demyelination, and Purkinje cell (PC) loss have been linked to tremors, impaired motor control, and loss of coordination. Similar pathologies have been observed in the mouse model of MS, experimental autoimmune encephalomyelitis (EAE). This study hypothesized that inflammatory demyelination of the cerebellum alters overall mitochondrial function and is a contributor to axon degeneration and PC loss. Postmortem cerebellar tissue from MS patients, particularly those with secondary progressive MS, showed decreased mitochondrial complex IV (COXIV) activity and significant PC loss. Inflammation, PC axon demyelination, axon degeneration, and parallel fiber loss were also evident. These findings were mirrored in late-stage EAE mice, which also showed increased inflammation and demyelination, reduced PC COXIV activity, and overall PC loss. Further analysis of EAE mice revealed altered mitochondrial structure, modified mitochondrial respiration, and reduced levels of mitochondrial genes involved in energy production. These findings indicate that both human MS and mouse EAE share similar cerebellar changes linked to mitochondrial dysfunction. Thus, late-stage EAE is a valuable model for studying MS-related cerebellar pathology, and mitochondria may be a potential therapeutic target for MS treatment.